Proses Entrepreneurial dalam Upaya Revitalisasi Budaya dan Industri di Kampung Batik Semarang: Suatu Studi Kasus untuk Pendidikan Entrepreneurship di STPKat Santo Fransiskus Asisi Semarang - Andarweni Astuti; Gunawan Gunawan (Jurnal Penelitian Pendidikan Agama Katolik, 2022)
The Indonesian government continues to struggle to overcome poverty, for example by distributing direct cash assistance to underprivileged families. These efforts are clearly not ideal. One of the initiatives that the government needs to continue to develop is to empower the small and medium enterprises (SMEs). One of the better examples of those empowerments is the revitalization of Kampung Batik Semarang. The goal of this research is to analyze the revitalization of Kampung Batik Semarang as an innovative, fruitful, and everlasting entrepreneurial process. The other goal is to provide a concrete and excellent case of entrepreneurial process for the students of STPKat Santo Fransiskus Semarang. The findings of the research: Kampung Batik Semarang is a model of a successful entrepreneurial process. The revitalizations of culture and industry are evident. New and everlasting working places were created. Everlasting, in sense that there is process of inheriting some unique motifs of the Batik.